(3EOGQI GdehGO hGdEeOGO ef GdfGMjI GdYdejI hGdYedjIs - (3YHO GdHGbj(B, (3UdGMs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3JfXje GOGQI GdehGOhGdGeOGO,GLQGAGJ GdehGO hGdGeOGO hGdOhQI GdeSJfOjI,JcGdja GOGQI GdehGO hGdGeOGO,JQejR hJUfja GdehGO hGdGeOGO,GdCUfGa hGdeNGRf,fXGe GdTQGA GdNGQLj,fXGe GSJNOGe GdMGSH GdBdj aj GOGQI GdehGO hGdGeOGO,fXGe GdQbGHI hGdeJGHYI Ydi eLGd eTJQjGJ JcOS GdeNRhf,GdfeGPL GdJMdjdjI,GdfeGPL GdGMJeGdjI,eTGcd Gdfbd hGdJhRjY,Jbjje GOGQI GdehGO hGdGeOGO(B.s
(3GdeQGLY U(B.463s
Keywords: (3EOGQI GdeNGRfs; (3EOGQI GdehGOs